A bibliometric analysis of Environmental, Social, Governance (ESG) and firm performance: A pathway to advancing SDG movement - Ag Kaifah Riyard Kiflee; Nornajihah Nadia Hasbullah; Nur hafidzah idris; Hazalinda Harun; Mohd Hafiz Bakar; Saiful Anwar (ResearchGate, 2024)
Objective: Companies engage in ESG (Environmental, Social, and Governance) activities to enhance financial returns and demonstrate adherence to market practices. Despite the existence of ESG, corporate performance is often in conflict due to inconsistent results and arguments. Theoretical Framework: Reflecting on that, this study uses a combination of bibliometric analysis and systematic literature review to examine the ESG literature and its impact on supporting the Sustainable Development Goals (SDGs). By utilising this approach, researchers can enhance their comprehension of ESG advancements by conducting quantitative bibliometric analysis and systematic review. Method: Thus, this study presents a bibliometric analysis covering articles obtained from the Scopus Database published between 2016 and 2022. The co-occurrence analysis includes 233 keywords from 50 articles relevant to the study was evaluated using VOSviewer software. Results and Discussion: The initial study concluded 121 articles related to ESG and corporate performance. This study opted for articles from the disciplines of business, management, and economics. As a result, 87 documents were selected. Co-authorship analysis showed that ESG analysis was associated with five main continents: Africa, the Americas, Europe and Oceania. Research Implications: An overview of trends and development directions is also provided in this study to visually show the current interest of the researcher in the topic. The analysis focuses on finding the best authors, the best journals, active institutions and the best citations of sustainable development research. Originality/Value: The bibliometric analysis effectively illustrates the evolution of ESG research and its potential to advance the SDGs, offering insights for future research in this field.